Non-destructive prediction of shoot-level leaf area and biomass in Indocalamus bamboo via scaling laws - Fu, Qinchao; Shi, Peijian; Gielis, Johan; Niklas, Karl J. (Frontiers in Plant Science, 2025)
This study addresses the critical need for efficient phenotyping methods in plant ecology by exploring predictive models for total leaf area per shoot (AT) and total leaf dry mass per shoot (MT), which are both key determinants of photosynthetic capacity and carbon allocation, using two fast-growing bamboo species (Indocalamus decorus and I. longiauritus) as proof of concept. Traditional approaches to measuring these traits are destructive and labor-intensive, motivating our exploration of non-destructive proxies based on one-dimensional leaf metrics. We validated the Montgomery equation for individual leaves, confirming a robust proportional relationship between leaf area (A) and the product of length and width (LW) in both Indocalamus species (k ≈ 0.72). Extending this to the shoot level, the Montgomery-Koyama-Smith equation (MKSE) revealed significant proportionality between total leaf area (AT) and the composite metric LKSWKS (where LKS denotes the sum of leaf widths and WKS denotes maximum leaf length, and the subscript “KS” stands for Koyama-Smith). However, power-law scaling analysis demonstrated allometric, non-isometric relationships for AT vs. LKSWKS (with a scaling exponent α < 1), indicating diminishing leaf area expansion per unit dimensional increase, and AT vs. total leaf dry mass (MT) (α < 1), indicating an increased biomass investment per unit area (i.e., increasing leaf mass per unit area) in larger shoots. These findings validate using simplified one-dimensional metrics that enable accurate, non-destructive predictions of shoot-level functional traits, advancing phenotyping in bamboo ecology, which may hold true more generally for other types of plant species.